Educational Values in the Novel Rumah Without Windows by Asma Nadia - Arum Puspitaningtyas; Anwar Effendi (Britain International for Academic Research (BIAR) Publisher, 2024)
This research is motivated by the phenomenon that the educational values instilled in the young generation today are still not optimal. This can be proven by the many cases of cheating committed by students when carrying out exams. This novel is suitable for use as teaching material because it contains many educational values that can be instilled in students. The aims of this research are (1) to find out the intrinsic elements that make up the Novel Rumah Without a Window by Asma Nadia, (2) to know the educational values depicted in the Novel Rumah Without a Window by Asma Nadia, and (3) to know the relationship between the Novel Rumah Without a Window Asma Nadia's work as an alternative teaching material in high school. This type of research is descriptive research with a literary pragmatics approach. The subject of this research is the novel Rumah Without Windows by Asma Nadia. Meanwhile, the object of this research is the educational values in the Novel Rumah Without Windows by Asma Nadia and their relation to literature teaching in high school. The main instrument in this research is the researcher himself or human instrument. The data collection method in this research was carried out using the reading and note-taking method. The theory used is Abrams' theory of literary pragmatics. The results of this research are (1) the intrinsic elements in the novel Rumah WITHOUT Window by Asma Nadia are characters, theme, setting, point of view, plot and language style. There are 22 characters in this novel with the main character named Rara. The theme of this novel is the strength of determination of a little girl to realize her dreams. The setting in this novel is divided into three, namely setting of place, setting of time, and setting of atmosphere. The point of view used in this novel is the point of view of the third person